Imagining Spaces Created for Queer Métis Youth - Fowler, Lucy (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2024)
Educational spaces, both formal and informal, are not always welcoming to queer Métis youth, especially to those youth who connect more to hip-hop cultures than those activities like jigging and beading which are often espoused as pillars in Métis culture. This article draws on conversations with youth, conducted as part of doctoral research using a visiting approach to data collection and analyzed using the voice-centered relational method. Through these frameworks, I created guideposts for developing educational spaces which are not just inclusive of but designed for queer Métis youth. These guideposts will be used in future development of Métis-focused hip-hop pedagogies and research with and for queer Métis youth.